Salud mental positiva, actitud hacia el aprendizaje y satisfacción en la formación de estudiantes de fisioterapia. - Alberto Soto-Manrique, Jesús; Horna-Zevallos, Beatriz; Martín Garay-Ugaz, Eduardo; Velásquez Vásquez, José Luis; Josefina Huayta-Franco, Yolanda (Revista de Investigación en Salud VIVE)
Mental health and attitudes towards learning are key factors in the educational development of students, especially in demanding disciplines such as physiotherapy. This research aims to analyze the relationship between positive mental health, attitudes towards learning, and satisfaction with practical training in physiotherapy students at a public university. A non-experimental and cross-sectional design was utilized, applying a quantitative approach that includes the Kolmogorov-Smirnov test, as well as analysis of p-values (p<0.05) and the likelihood ratio test. The proposed hypothesis suggests that positive mental health and favorable attitudes towards learning are positively associated with greater satisfaction in practical training. The results indicate that 50% of the students show high levels of positive mental health, 79.6% exhibit positive attitudes towards learning, and 62.1% express high satisfaction with their practical training. The Kolmogorov-Smirnov test confirms that the data do not follow a normal distribution. The model coefficients are significant (p<0.05), indicating the relevance of both the independent and dependent variables, as well as their dimensions. Additionally, the likelihood ratio test reveals high significance (p = 0.000), supporting the acceptance of the hypothesis. Furthermore, Pearson values and deviations are also significant (p < 0.05). In conclusion, positive mental health and attitudes towards learning have a significant effect on the academic performance of students.